2017
DOI: 10.5489/cuaj.4786
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative sarcopenia status is associated with lymphovascular invasion in upper tract urothelial carcinoma patients treated with radical nephroureterectomy

Abstract: Introduction: Sarcopenia is a novel concept representing skeletal muscle wasting and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…As Figure 2 shown, the synthesized result suggested that sarcopenia was significantly associated with poor OS (Fixed-effect model, HR 1.73, 95% CI: 1.48–2.01, P <.05; heterogeneity: P = .064; I 2 = 40.5%). Additionally, there were 10 eligible studies with 1790 patients [2326,28,29,32,4042] that evaluated the relationship between sarcopenia and CSS in urologic tumors. Our synthesized analysis of these studies showed that there was also a significant correlation between sarcopenia and poor CSS (Fixed-effect model, HR: 1.85, 95% CI: 1.51–2.28, P <.05, heterogeneity: P = .053; I 2 = 46.2%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As Figure 2 shown, the synthesized result suggested that sarcopenia was significantly associated with poor OS (Fixed-effect model, HR 1.73, 95% CI: 1.48–2.01, P <.05; heterogeneity: P = .064; I 2 = 40.5%). Additionally, there were 10 eligible studies with 1790 patients [2326,28,29,32,4042] that evaluated the relationship between sarcopenia and CSS in urologic tumors. Our synthesized analysis of these studies showed that there was also a significant correlation between sarcopenia and poor CSS (Fixed-effect model, HR: 1.85, 95% CI: 1.51–2.28, P <.05, heterogeneity: P = .053; I 2 = 46.2%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, in this retrospective study, patients with sarcopenia were significantly older than those without sarcopenia in the UTUC patient group treated with RNU. Many studies have reported the prognostic significance of sarcopenia for UTUC patients who underwent RNU [1][2][3] by comparing the outcomes of sarcopenic and non-sarcopenic patients. However, these studies did not evaluate another important condition that frequently occurs in cancer patients-cachexia.…”
Section: Plos Onementioning
confidence: 99%
“…Thus, identifying high-risk patients as candidates for adjunctive therapies is important to improve oncological outcomes. Host factors play an important role, but tumor factors including the pT and pN stages, tumor grade, and lymphovascular invasion are essential [1][2][3].…”
Section: Introductionmentioning
confidence: 99%